THE CONCEPT OF EVIDENCE-BASED MEDICINE: HOW FAR IS MY PRACTICE FROM THE STANDARD? (Iraqi Journal of Medical Sciences, 2017)
Clinical judgment and long experiences, reading textbooks and scientific journals, in addition to conferences and personal beliefs are generally sources for physician management plan, however; errors in clinical reasoning and gaps in evidence were described since long time. For which evidence based strategy had been applied in medical practice aiming to improve the decision-making skills of individual physicians to individual patients. Evidence base medicine (EBM) is a systematic approach to clinical problem solving which make use of the best research evidence in term of clinical expertise and patient values. Keywords:Evidence-based medicine DOI: 10.22578/IJMS.14.4.1
Keywords: Evidencebased medicine